IMPLEMENTATION OF TEACHING AND LEARNING APPROACHES FOR INFANTS AND TODDLERS IN CHILDCARE CENTRES (TASKA): ADDRESSING MODERN PARENTS' ASPIRATIONS - NURUL SHAHANA KHIRIZAL; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This is a literature review of modern day teaching and learning strategies in childcare centers (TASKA) of infants and toddlers with specific reference to how the teaching and learning strategies are correlated with the contemporary desire of parents. According to the analysis, effective TASKA initiatives have begun to embrace relationship-based, play-based pedagogies with a family collaboration strategy and professional workforce development. The main strategies encompass responsive models of care that emphasize safety, developmentally adequate practice, and shared care with families.